Application of Laser Capture Microdissection to Craniofacial Biology: Characterization of Anatomically Relevant Gene Expression in Normal and Craniosynostotic Rabbit Sutures. (January 2017) - Rottgers, S. Alex; Gallo, Phillip; Gilbert, James; Macisaac, Zoe; Cray, James; Smith, Darren M.; Mooney, Mark P.; Losee, Joseph; Kathju, Sandeep; Cooper, Gregory
Objective: Fusion of the cranial sutures is thought to depend on signaling among perisutural tissues. Mapping regional variations in gene expression would improve current models of craniosynostosis. Laser capture microdissection (LCM) isolates discrete cell populations for gene expression analysis. LCM has rarely been used in the study of mineralized tissue. This study sought to evaluate the potential use of LCM for mapping of regional gene expression within the cranial suture. Design: Coronal sutures were isolated from 10-day-old wild-type and craniosynostotic (CS) New Zealand White rabbits, and LCM was used to isolate RNA from the sutural ligament (SL), osteogenic fronts (OF), dura mater, and periosteum. Relative expression levels for Fibroblast Growth Factor 2 (FGF2), Fibroblast Growth Factor Receptor 2 (FGFR2), Transforming Growth Factor Beta 2 (TGFβ-2), Transforming Growth Factor Beta 3 (TGFβ-3), Bone Morphogenetic Protein 2 (BMP-2), Bone Morphogenetic Protein 4 (BMP-4), and Noggin were determined using quantitative real-time PCR. Results: A fivefold increase in TGFβ2 expression was detected in the CS SL relative to wild type, whereas 152-fold less TGFβ-3 was detected within the OF of CS animals. Noggin expression was increased by 10-fold within the CS SL, but reduced by 13-fold within the CS dura. Reduced expression of FGF2 was observed within the CS SL and dura, whereas increased expression of FGFR2 was observed within the CS SL. Reduced expression of BMP-2 was observed in the CS periosteum, and elevated expression of BMP-4 was observed in the CS SL and dura. Conclusions: LCM provides an effective tool for measuring regional variations in cranial suture gene expression. More precise measurements of regional gene expression with LCM may facilitate efforts to correlate gene expression with suture morphogenesis and pathophysiology.